Gonzalo Mayo y Ciro Alegría: adaptación de la novela El mundo es ancho y ajeno (1941) a la historieta (1963-1965) - Suárez Ramos, Maria Jimena (2025)
The present study analyzes the adaptation of the novel Broad and alien is the world to the comic by Gonzalo Mayo and Ciro Alegría. Based on the formal analysis method and the theory of adaptation, it is proposed that the comic Broad and alien is the world adds meanings to the original sense of the novel; such as an iconography of a national character, representative and claiming of the Andean and peasant world; an idea of national representation that joins Andean local elements to American cultural influence and European art tradition; and a discursive distance of Gonzalo Mayo regarding the script and the novel.